Marketing digital en la Microempresa Romano Market en la ciudad de babahoyo del periodo 2023. - De Lucca Quiñonez, Karina Vanessa (2025)
Today, digital marketing is the tools that companies need if they want to reach a wide but diverse audience, and that is precisely what it provides. Due to the capabilities of this tool, companies can offer services and products in real time to customers, understand their needs and preferences, and provide them with personalized experiences tailored to what is happening for them at the moment. El Romano Market is a recognized private micro-business in the city of Babahoyo whose products have been praised by many of our consumers due to their quality and customer-centric approach; Furthermore, this micro-business has been established in the market for 35 years. Therefore, this case study aims to analyze the marketing strategies of Romano Market. For this purpose, we will also promote your presence on all types of digital platforms so that people know you and purchase your products. The Romano Market microbusiness has an extensive product catalog and good customer service, but it does not generate online sales from its digital media. Therefore, we are recommending in our case study to use new digital marketing strategies that must be viable because, through surveys carried out with their regular consumers, they expressed that they want to receive advertisements by email and text messages, that the company is online often and can be contacted from anywhere it is. For this reason, digital marketing is very important in companies because it helps satisfy the needs of consumers and potential customers.